Effects of diet supplemented with water extracts of Artemisia annua L. on small intestinal immune and antioxidative indexes in lambs - Gang, Gen; Gao, Ruiheng; Zhao, Huricha; Jin, Xiao; Xing, Yuanyuan; Hong, Lei; Yan, Sumei; Xu, Yuanqing; Shi, Binlin (Frontiers in Veterinary Science, 2025)
IntroductionArtemisia annua L., an herbaceous plant, belong to the Artemisia genus within the Asteraceae family. Due to its significant medicinal properties, it has emerged as a focal point of research in the field of animal production. In the present study, the responses of intestinal immune and antioxidative indexes, and the related gene expression to water extracts of Artemisia annua L. (WEAA) supplementation in diet were profiled in lambs.MethodsIn total, 32 female lambs (Dorper × Han), with eight replicates per group, were randomly assigned to four treatment groups. These groups were created by supplementing 0, 500, 1,000, and 1,500 mg/kg WEAA to the basal diet, respectively.ResultsThe results showed that WEAA addition increased sIgA, IgG, IL-1β, IL-2 and IL-4 levels in the duodenal and jejunal mucosa in a manner that was dependent on the dosage (p < 0.05). Moreover, WEAA promoted the expression of factors (TLR4, MyD88, IKKβ, IκBα, NF-κB p50, NF-κB p65, IL-1β and IL-4) related with the TLR4/NF-κB pathway, thus improving small intestinal immune function, thereby showing peak effects in the 1,000 mg/kg WEAA group. Additionally, WEAA supplementation also enhanced antioxidative function through the Nrf2/Keap1 pathway in the small intestinal mucosa, particularly by increasing GSH-Px and CAT concentrations and decreasing MDA content in a manner that was dependent on the dosage (p < 0.05), with maximal effects observed in the 1,000 mg/kg group. Furthermore, expressions levels of Nrf2, GSH-Px and HO-1 in the small intestine increased quadratically (p < 0.05), while Keap1 expression levels exhibited a downward quadratic trend (p < 0.10).ConclusionIn summary, the optimal dietary addition of 1,000 mg/kg WEAA significantly enhanced intestinal immune function, antioxidant capacity, and the expression of related genes in the intestinal mucosa of lambs.